Love thy neighbour or opposites attract? Patterns of spatial segregation and association among crested penguin populations during winter. (5th February 2014) - Ratcliffe, Norman; Crofts, Sarah; Brown, Ruth; Baylis, Alastair M. M.; Adlard, Stacey; Horswill, Catharine; Venables, Hugh; Taylor, Phil; Trathan, Philip N.; Staniland, Iain J.; Manne, Lisa
ABSTRACT Aim Competition for food among populations of closely related species and conspecifics that occur in both sympatry and parapatry can be reduced by interspecific and intraspecific spatial segregation. According to predictions of niche partitioning, segregation is expected to occur at habitat boundaries among congeners and within habitats among conspecifics, while negative relationships in the density of species or populations will occur in areas of overlap. We tested these predictions by modelling the winter distributions of two crested penguin species from three colonies in the south‐western Atlantic. Location Penguins were tracked from two large colonies on the Falkland Islands and one in South Georgia, from where they dispersed through the South Atlantic, Southern Ocean and south‐eastern Pacific. Methods Forty macaroni penguins (Eudyptes chrysolophus) from South Georgia and 82 southern rockhopper penguins (Eudyptes chrysocome chrysocome) from two colonies in the Falkland Islands were equipped with global location sensors which log time and light, allowing positions to be estimated twice‐daily, from April to August in 2011. Positions were gridded and converted into maps of penguin density. Metrics of overlap were calculated and density was related to remote‐sensed oceanographic variables and competitor density using generalized additive models. Results Macaroni penguins from western South Georgia and southern rockhopper penguins from Steeple Jason Island, Falkland Islands, were spatially segregated by differences in their habitat preferences thus supporting our first prediction regarding interspecific segregation. However, southern rockhopper penguins from Beauchêne Island showed a marked spatial overlap with macaroni penguins as the two had similar habitat preferences and strong mutual associations when controlling for habitat. Contrary to our predictions relating to intraspecific segregation, southern rockhopper penguins from Beauchêne Island and Steeple Jason Island were segregated by differences in habitat selection. Main conclusions Morphological differentiation probably allows macaroni penguins from South Georgia and southern rockhopper penguins from Beauchêne Island to coexist in areas of spatial overlap, whereas segregation of the two Falkland rockhopper penguin populations may have arisen from two distinct lineages retaining cultural fidelity to ancestral wintering areas.